Analisis Stakeholder dalam Penanggulangan Pertambangan Emas Tanpa Izin (PETI) di Kabupaten Merangin - Mirza Sazeta (Journal of Demography, Ethnography and Social Transformation, 2022)
Unlicensed Gold Mining Activity (PETI) is one of the problems that has not been resolved by the government yet. One mining area that has PETI activities is Merangin District. This study aims to find out who the stakeholders are involved and how their roles are, as well as identify the factors that are obstacles for stakeholders in overcoming the activities of PETI. This study will use the Base of Power-Directions of Interest to identify stakeholder influences and interests, and Power vs Interest Grid to see stakeholder positions based on power and interests. The results showed that the handling of PETI activities in Merangin District was still carried out by the local government and each stakeholder had different power and interests. The stakeholders who had the greatest influence in the socialization were the Environmental Office of Merangin District, the Merangin Regional Police was the most important stakeholder in eradication, and the sub-district government was the stakeholder who had the important role in land rehabilitation.